Impact of audit committee and audit quality on preventing earnings management in the pre- and post- Nigerian corporate governance code 2011 - Miko, Nuraddeen Usman; Kamardin, Hasnah (Elsevier Ltd., 2015)
Earnings management have been considered as one of the methods used by the business leaders to mislead their stakeholders to report unrealistic numbers, despite the various check and balances (e.g. corporate governance code) on the process.Nigeria experienced two corporate governance codes issued by SEC, code 2003 and code 2011.This study tends to measure the effectiveness of these two codes and make comparisons using audit committee and audit quality against earnings management in the pre- and post-code 2011.